Organizational contextual factors, budget participation, commitment and performance of China public universities - Tang, Yiwen (2023)
Budget and performance issues in the public sector have become the focus of the Chinese government's attention. As non-profit institutions, Chinese public universities receive the majority of their funding from government grants; consequently, they must pay attention to the development issues of budget participation and performance. Most previous research has focused on the budget participation and performance of businesses while neglecting that of universities, especially Chinese public universities. The performance of a university affects its resources and development, meaning that studying the factors affecting its budget participation and performance plays a crucial role in improving its competitiveness. Therefore, the purpose of this study is to comprehensively explore the factors influencing the budget participation and performance of public universities in China. Specifically, this study examines the relationship between contextual factors, budget participation, organizational commitment, and performance in the public universities. Influenced by contextual factors such as environment, culture and budget, the performance of Chinese public universities still has substantial room for improvement compared with their foreign counterparts. Organizational commitment, which is often ignored in practice, should be emphasized to improve employees' enthusiasm towards budget participation and performance. Based on contingency theory, contextual factors are divided into information asymmetry, budget emphasis, organizational culture, and environmental uncertainty. Organizational commitment is proposed to play a moderating role, as per the identity theory. A total of 849 public universities in China are selected using the census sampling method, from whom data is collected through a questionnaire survey. The research unit is the university, whereby one questionnaire represents one university. Data from a total of 315 valid questionnaire responses is analyzed using PLS-SEM. Based on the empirical analysis results, this study finds that: budget participation has a positive and significant effect on performance; contextual factors indirectly affect performance through the mediating effect of budget participation; and organizational commitment has a moderating effect between budget participation and performance. Notably, the hypothesis that contextual factors significantly impact the performance of public universities is only partially supported, as the impact of environmental uncertainty on performance is not significant. While previous studies have mainly focused on enterprises, this study chooses the context of public universities and reveals that public universities and enterprises have different attitudes towards contextual factors. In addition, this study takes budget participation as a mediating variable to provide further insight into its influencing factors and outcomes from a more comprehensive perspective, which is a useful contribution to existing knowledge. This finding also extends the application of contingency theory and identity theory to explain the factors affecting the performance of Chinese public universities. To sum up, this study provides an empirically proven framework to help public universities form an effective, performance-enhancing system. This study considers the factors affecting budget participation and performance from a comprehensive perspective, which has reference value for performance improvement in public universities and the education industry as a whole.